Les enfermements d’un vagabond criminel. Vacher, tueur de bergers - Marc Renneville (Criminocorpus)
This contribution proposes to give an account of the succession of confinements experienced by a serial killer who was essentially presented and represented as the typical vagabond, a great walker and free to move about, perpetuating a “bloody odyssey”. Joseph Vacher (1869-1898) nevertheless experienced the main institutions of confinement at the end of the 19th century: school, religious congregation, barracks, asylum and prison. How did he experience them and what role did these experiences play in his perception of the world? Secondly, we will ask to what extent these confinements contributed, after Vacher’s arrest, to the reflection on the motives for his act? In conclusion, we will point out the difficulty of accessing the subjectivity of our objects of study because this approach implies, for the historian, a return to oneself and a deconstruction of transmitted memories.